A functional equation from Kyrgyzstan

preview_player
Показать описание
🌟Support the channel🌟

🌟my other channels🌟

🌟My Links🌟

🌟How I make Thumbnails🌟

🌟Suggest a problem🌟
Рекомендации по теме
Комментарии
Автор

Letting p(x) = x^2 + x + 3, we have x^2 - 3x + 5 = p(1-x), so the functional equation is f(p(x)) + 2f(p(1-x)) = 6x^2 - 10x + 17. But letting x = 1- x, we get f(p(1-x)) + 2f(p(x)) = 6x^2 - 2x + 13.

These two equations let us solve for f(p(x)) = 2x^2 + 2x + 3 = 2p(x) - 3. Letting y = p(x) gives f(y) = 2y - 3.

So f(2009) = 4015

skerJG
Автор

Hi Michael, are you planning on covering any of the 2022 IMO problems?

lilylikesmarkies
Автор

There’s a typo at 9:30. You should have q(x)=p(x)-4x+2, meaning that q(x_0)=2011-4x_0 and p(x_1)=4x_1+2007. Then everything checks out.

tiripoulain
Автор

I skipped a lot of those steps by starting simply setting x = -x + 1 in the original equation. That kind of made the two polynomials on the left hand side to basically switch places. From there I just solved it as a simple linear system and got:

f(x² - 3x + 5) = 2x² - 6x + 7

Then I found a solution to:
x² - 3x + 5 = 2009

and set x to that in the previous expression to get f(2009) = 4015

kuronno
Автор

Usually when Michael solves a functional equation, he starts by trying some values of the variable(s). So, start with x = 0, and you get f(3) + 2 f(5) = 17. OK, try another. If x = 1, you get
f(5) + 2 f(3) = 13. That's too symmetrical to ignore. Solving the system gets you f(3) = 3 and f(5) = 7. If you assume that f is linear, you're virtually done, but that's probably too much of a leap. So try more values of x. x = -1 leads to f(3) + 2 f(9) = 30. We already know f(3), so that leads to f(9) = 15. x = 2 also leads to f(9), but x = -2 leads to f(15) = 27.

So we have:

x f(x)
3 3
5 7
9 15
15 27

That's "definitely" linear -- f(x) = 2x - 3 -- though it's not a proof. To prove it, show that it solves the original function equation. That should be good enough for the judges.

jonpress
Автор

doesn't it pretty easily follow from the first step that f(x)=2x-3?

fefeisbored
Автор

Try factoring the argument polynomials:

*p(x) := x^2 + x + 3 = (x + 1/2)^2 + 11/4*
*q(x) := x^2 - 3x + 5 = (x - 3/2)^2 + 11/4*

We notice translation- and mirror-symmetry between *p(x), q(x)* :

*x in R: q(x) = p(x - 2) = p(1 - x)*

Using the short-hand *g(x) := f(p(x))* and the mirror-symmetry above the functional equation simplifies to

*x in R: g(x) + 2g(1 - x) = 6x^2 - 10x + 17*

A change of variables " *x -> 1 - x* " leads to a second functional equation:

*x in R: g(1 - x) + 2g(x) = 6x^2 - 2x + 13*

Using both functional equations we can actually solve for *g(x)* :

*x in R: g(x) = 2x^2 + 2x + 3 = 2p(x) - 3 = f(p(x))*

Setting *x := -1/2 + 5/2 * \sqrt{321}* such that *p(x) = 2009* we finally have

*f(2009) = 2 * 2009 - 3 = 4015*

carstenmeyer
Автор

Nice to see problems from my homecountry!Thx for the video

Abc-npeo
Автор

This problem is one of the best. Thanks for the solution! By the way, for the solution of p(x) = 2009 and q(x) = 2009, it's sqrt(321), not sqrt(312).

khiemngo
Автор

Differentiation of both sides by x leads to df/dy=2 when y is composite argument. So, f(y)=2y+C. The substitution f(x)=2x+C to equation makes C=-3.

izgirft
Автор

Let r=x^2+x+3, s=x^2-3x+5, t=6x^2-10x+17
Then from above: 2r+4s=t+9
Substitute back to the original expression: f(r)+2f(s)=t=2r+4s-9
This is a simple functional equation problem,
Let (r, s)=(0, 0) then f(0)=-3
Let (r, s)=(free, 0) then f(r)=2r-3

zh
Автор

this was my approach:
let x^2+x+3=X
and x^2-3x+5=Y


suppose 6x^2-10x+17=aX+bY+c

after some algebra involving a, b and c. you get

f(X)+2f(Y)=2X+4Y-9

sub in Y=X to get f(x)=2x-3

-Curved
Автор

a, b and c are real numbers st ab+bc+ca=1
Show that :
(a+1/b)^2 +(b+1/c)^2 + (c+1/a)^2 > 16

zeggwaghismail
Автор

hmmm at 3min10 it's very obvious that f(x) = 2x - 3 satisfies the entire functional equation

so f(2009) = 2*2009 - 3 = 4015

lol

julienmallet
Автор

Hi michael, i have a suggestion : imo 2022 p2, and imo 2022 p5

ianteles
Автор

In my opinion it is simpler if you perform the change of variable x -> x+1, then the equation writes as f(x^2 + 3x +5) + 2 f(x^2 -x + 3) = 6 x^2 + 2x +13. Then another change of variable x-> -x and now the equation becomes f(x^2 - 3x +5) + 2 f(x^2 + x + 3) = 6 x^2 - 2x +13.
Using the original equation you can find f(x^2 + x +3) = 2 (x^2 + x + 3) - 3. Setting x^2 +x +3 = 2009 you obtain f(2009) = 2 * 2009 - 3 = 4015

maxmartinelli
Автор

I have a completely different approach..but it's a bit calculative!!
at first, put x = ( sqrt(8025) --1)/2 in the given eqn to get
f( 2013-- 2*sqrt 8025) +2f(2009) = a numerical value ....(1)
Then put x =(3--sqrt 8025)/2 in the eqn to get
f(2009) + 2f (2013--2*sqrt 8025)= another numerical value
from the above eqns (1) and (2), we easily get the required value of f(2009)
[this process is a bit calculative]

jerrymouse
Автор

i think i did it way easier. Put x=y-2 into equation and then put x= -y-1 into equation. This gives us two linear equations with two unknown terms, we solve it to immediately get f(y^2-3y+5] =2y^2-6y+7. Therefore if we want f(2009] we take y such that y^2-3y+5=2009.
So y^2-3y=2004, so 2y^2-6y=4008, so f(2009]=4015

Szynkaa
Автор

I substituted x=0, and then x=1, to get two different equations:

f(3) + 2f(5) = 17
2f(3) + f(5) = 13

solving this gives f(3)=3 and f(5)=7. I didn't assume that f(x) was linear, but if I did I could have found that f(x) = 2x - 3 and substituted in 2009 to get 4015.

pNsB
Автор

I did this problem more numerically, generating values for f(x) by plugging in values for x such as 0 and 1. Then I found the x-value for which the “interior polynomials” were equal, which was at x=0.5, y = 3.75. Using that I was able to get a third vale of f(15/4)=9/2. Using f(3)=3 and f(5)=7, I used a matrix and assumed a quadratic form for f(x). The solution revealed a linear function, f(x)=2x-3 for which I evaluated it at x=2009 to get the solution. Great problem! Love it

figuritout